Cultural Landscape, Urban Settlement and Dweller's Perception: A Case Study of a Vernacular Village in Northern Thailand - Junjira Nunta; Nopadon Sahachaisaeree (My University, 2012)
This research attempts to investigate factors affecting the formational pattern of cultural landscape and the formation of urban settlement resulting from the shifting communal needs in the historical and theoretical facets. It endeavors to elucidate the linkages between the behavioral–functional solution and the physical/spatial settings of cultural landscape. The research indicates that urbanization affected the formation of urban settlement and the changes in dwellers' perceptions. Perception of the local dwellers should be the prime factor to be considered in the planning and management of urban settings.
Keywords: Settlement (finance); Human settlement; Cultural landscape; Urban landscape; Architectural and Urban Studies